2021
DOI: 10.5194/esd-12-469-2021
|View full text |Cite
|
Sign up to set email alerts
|

The half-order energy balance equation – Part 1: The homogeneous HEBE and long memories

Abstract: Abstract. The original Budyko–Sellers type of 1D energy balance models (EBMs) consider the Earth system averaged over long times and apply the continuum mechanics heat equation. When these and the more phenomenological box models are extended to include time-varying anomalies, they have a key weakness: neither model explicitly nor realistically treats the conductive–radiative surface boundary condition that is necessary for a correct treatment of energy storage. In this first of a two-part series, I apply stan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…A1, we then calculated spatial zonal and meridional fluctuations loga( x) and loga( y), and from these their root mean square (rms) values were calculated. From the figure, we see that to a good approximation, log a ( x) ≈ x L EW The fluctuations are Haar fluctuations, but because H x ≈ H y > 0, they are nearly equal to difference fluctuations (Lovejoy and Schertzer, 2012). We see that the zonal and meridional lines are roughly parallel, with a "trivial" horizontal anisotropy factor ≈ 5 (typical north-south fluctuations are 5 times larger than typical east-west ones).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A1, we then calculated spatial zonal and meridional fluctuations loga( x) and loga( y), and from these their root mean square (rms) values were calculated. From the figure, we see that to a good approximation, log a ( x) ≈ x L EW The fluctuations are Haar fluctuations, but because H x ≈ H y > 0, they are nearly equal to difference fluctuations (Lovejoy and Schertzer, 2012). We see that the zonal and meridional lines are roughly parallel, with a "trivial" horizontal anisotropy factor ≈ 5 (typical north-south fluctuations are 5 times larger than typical east-west ones).…”
Section: Discussionmentioning
confidence: 81%
“…This two-part paper re-examined the classical heat equation with classical semi-infinite geometry. In the horizontally homogeneous case (Part 1, Lovejoy, 2021), the fundamental novelty is the treatment of the conductive-radiative boundary conditions; here (Part 2), it is the use of Babenko's method to extend this to the more realistic horizontally inhomogeneous problem. In both cases, the semi-infinite subsurface geometry is only important over a shallow layer of the order of the diffusion depth where most of the storage occurs (roughly estimated as ≈ 100 m in the ocean and ≈ < 10 m over land; see Table 1 and Appendix…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this cannot be assured, adaptive methods (as the MEMD) could be more suitable for reducing some mathematical assumptions and a priori constraints (Huang et al, 1998;Huang and Wu, 2008;Rehman and Mandic, 2010). Moreover, geophysical data are usually also characterized by scale-invariant features over a wide range of scales with different complexity and show a scale-dependent behavior due to several factors like forcings, coupling, intrinsic variability, and so on (e.g., Lovejoy and Schertzer, 2013;Franzke et al, 2020). For the above reasons, in this work we put forward a novel approach based on combining two different data analysis methods for investigating the multiscale fractal behavior of the coupled oceanatmosphere system: multivariate empirical mode decomposition (MEMD; Rehman and Mandic, 2010) and generalized fractal dimensions (Hentschel and Procaccia, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, by means of a 36-variable model displaying marked LFV Vannitsem et al (2015) demonstrated that the LFV in the atmosphere could be a natural outcome of the ocean-atmosphere coupling. Other sources could be invoked to explain and to contribute to the development of LFV in the atmosphere, such as the long-range system memory as a consequence of the heat storage mechanism of the land-ocean-atmosphere system (e.g., Lovejoy, 2021;Lovejoy et al, 2021), the internal dynamics of the atmosphere itself (e.g., Legras and Ghil, 1985), or even the interaction between the tropical and extratropical regions (e.g., Alexander et al, 2002;Vannitsem et al, 2021), just to quote a few.…”
Section: Introductionmentioning
confidence: 99%